Effects of fish size, feeding rations and vitamin C supplement on growth performance and immune responses of waigieu sea perch (Psammoperca waigiensis) at juvenile stage : - Masengesho, Barthazar (Can Tho university, 2018)
This book introduce about to evaluate the effect of feeding ration on growth performance of Waigieu. Determine the impact of vitamin C supplement on growth performance and immune responses of Waigieu Sea perch (Psammoperca waigiensis) juvenile.